(untitled) (Gestão & Regionalidade, 2025)
The job market today is looking for professionals with, in addition to technical capacity, skills that are important in the 21st century, such as entrepreneurship. Universities and higher education institutions play an important role in shaping the professional profile demanded by the labor market. Therefore, adjustments are needed in the teaching and learning process that help the student to build such skills. Thus, this article aims to analyze how the national and international scientific literature has portrayed the use of active methodologies in the classroom in higher education institutions, for Entrepreneurial Education. For this, a systematic review of the literature was carried out in the Scopus database. The results point to a growing interest in the subject and these methods have developed fundamental entrepreneurial skills in students in the contemporary context. The most active teaching-learning methods found were Design Thinking and Project-Based Learning.